Does FDI promote the resource curse in Nigeria? - Olatunji Abdul Shobande (Journal of Risk and Financial Management, 2022)
This study investigated whether Foreign Direct Investment (FDI) supported the resource curse hypothesis in Nigeria. The precise methodological contribution was based on the Vector Error Correction and Granger causality test. The finding showed cointegration among the variables, whereas the speed of adjustment was slightly low. Similarly, natural resource to gross domestic product, FDI, and exchange rate unidirectionally Granger cause economic welfare, whereas bidirectional Granger causality is observed between indicators of natural resources to export, trade, and economic welfare. The results clearly indicate that FDI and natural resource management could improve economic wellbeing, although with a cost of volatility in the exchange rate and utilisation of resources. Thus, the study recommends the urgent need for effective and efficient management of the country's natural resources to attract foreign direct investment and generate growth that can contribute meaningfully to the welfare of the citizens. Likewise, there is a need to diversify oil resources to other non-natural resources for the economy to stimulate growth and reduce the vulnerability of the economy to external shocks.
Keywords: 650; Granger causality; economic welfare; FDI; natural resources; Nigeria; resource curse